Formal credit institutions in agriculture of Kazakhstan (micro-econometric analysis) - Sholpan Gaisina (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
The financing of agricultural producers is one of the most acute problems along the entire scope of economic reforms in Kazakhstan. The issue is: What kind of financial sources could maintain the development of agricultural production? Internal sources such as profit, depreciation capital, and various reserve and insurance funds can not be considered as a key financial base. State financial support of agriculture in Kazakhstan (which plays a significant role in the most developed countries), is episodic in nature, small in size and typically does not reach the recipients. In these circumstances, a potential supplier of financial and investment resources could be a banking system and such non-banking credit institutions as credit cooperatives. Econometric analysis is used to analyze the determinants of credit access. Results suggest that access to subsidized credit has a significant role in determining access to bank credits and investment activity of agricultural enterprises. Major determinants of credit rationing are the size of arable land possessed by the agricultural enterprise and the cost of equipment, expressing an ability of borrower to use them as collateral.
Keywords: G21; O16; Q14; 330; agricultural finance; credit rationing; micro-econometrics analysis